Can Integrated Social Protection Programmes Affect Social Cohesion? Mixed-Methods Evidence from Malawi - Francesco Burchi; Federico Roscioli (The European Journal of Development Research, 2022)
Through a sequential mixed-methods approach, the paper investigates the effects of the different components of the Tingathe Economic Empowerment Programme (TEEP) on social cohesion in Malawi. The TEEP is an integrated social protection scheme offering to three different groups these services: a lump-sum transfer, a financial/business training connected to the creation of saving groups, and a combination of both. While other studies assessed the impacts of similar programmes on other outcomes, none focussed on social cohesion. The econometric analysis shows no concrete effect of the lump-sum, while both training and participation in savings groups affect within-group trust and cooperation. The qualitative analysis reveals a decline in trust towards local institutions and other village members; however, this was not related to the TEEP but to the social cash transfer (SCT) on whose infrastructure the TEEP rests. Other village members considered unfair that the beneficiaries received the SCT and this caused tensions.
Keywords: 330; Social protection; Social cohesion; Graduation programmes; Mixed methods; Malawi; Economics